Barriers and opportunities for the transition to a circular economy. A case study of Chilean cooperatives - Cea Valencia, Jorge (2020)
The linear use–consumption–waste production model does not make allowances for resource limitation or loss, or the associated pollution. The concept of the circular economy (CE) emerged as an alternative to this model. In recent times, the CE has awoken considerable interest and discussion among academics, enterprises, and governments given its connection with sustainable development and its potential impact on the economic, social, and environmental levels. At present there is no precise and established definition of the CE as a concept, and though this new paradigm could proffer a host of benefits for the organizations who integrate it into their business model, it might also bring about difficulties or challenges. The main aim of this study is to identify barriers and opportunities for the transition to the CE based on a case study of cooperatives in Chile. The study employs the qualitative methodology of social discourse analysis, complemented by a literature review and interviews with CE experts. Five categories were constructed to guide the interviews and subsequent analysis: (i) knowledge, (ii) technological, (iii) structural, (iv) operational, and (v) financial. A total of ten interviews were conducted across the three specific cases selected. The data analysis was conducted using Atlas TI8 software. The results obtained for each case study point to gaps and opportunities in the five categories, and, more generally, in the legal and cultural spheres.